Urban Tourism Concepts in the Design of Kampung Tua in Batam - Yusra Aulia Sari; Mulia Pamadi (TATALOKA, 2022)
Batam City’s government has focused on exploring its tourism potential in recent years. This makes Batam the 3rd largest city in the number of tourist arrivals after Bali and Jakarta. Batam is one of the cities that is trying to develop the potential of an old village. There are at least 37 areas that have been agreed upon by the government and the community as Kampung Tua. Kampung Tua is a group of houses that function as neighborhoods the original inhabitants of Batam City when Batam began to be built, containing historical values, local culture, or religion that were preserved. This research aims to determine the design of the concept of urban tourism in Kampung Tua Tanjungriau. The method used in this research is the qualitative approach. Data collection was performed with observation, documentation, literature study, and data from local government. The result of this research is the design of urban tourism in Kampung Tua Tanjungriau such as physical and non-physical components of the Kampung Tua Tanjungriau area which has an interesting collaborative design between urban design and urban tourism.